Selecting students to a dormitory using AHP - Narabin, Santit; Boonjing, Veera (My University, 2016)
A dormitory is an accommodation service of a university for the students especially who live far away from the educational institutions. In our country, with perfectly low price, a dormitory is needed for number of students. Each year student applicants are selected by a committee. It can be happened that a group of students may not be selected by a committee member without a reasonable reason. This fact can bring undesirable biases in educational area. Therefore, using rational and acceptable criteria for selecting students to stay in a dorm are needed. In this article, we propose to apply Analytical Hierarchy Process (AHP) as a Decision Support System (DSS) to select undergraduate students to a dormitory of a university. We provide 4 main criteria and 16 sub-criteria. Based on the method, an eigenvector is calculated and the Consistency Ratio (CR) can be determined from the eigenvector. By iteratively following the process of AHP, we then can have appropriate weight numbers that can be used for selecting proper students to the dormitories.
Keywords: Analytical Hierarchy Process (AHP); Decision Support System; Multi-Criteria Decision Making